Distributed Secondary Control Strategy Against Bounded FDI Attacks for Microgrid With Layered Communication Network - Wang, Fuzhi; Shan, Qihe; Teng, Fei; He, Zhiqiang; Xiao, Yang; Wang, Zhiyu (Frontiers in Energy Research, 2022)
This paper investigates FDI attacks in distributed secondary control strategy for low inertia microgrid with a high proportion of renewable energy and power electronics. Adversaries always aim to tamper information exchange between the neighbor distributed generators (DGs) in microgrids, which results in voltage and frequency deviation leading to power breakdown. To enhance the resilience against FDI attacks of microgrid, a control network layer interconnecting with the original data transmission layer is introduced to form a layered communication network. Due to the higher openness of the layered network, the introduced control network layer also faces to potential FDI attacks. This paper proposed a distributed secondary control strategy against double-layered bounded FDI attacks rather than only attacks in the information transmission layer. The strategy can mitigate FDI attacks launched in the control network layer, and adverse influence on the data transmission layer can also be mitigated caused by FDI attacks launched in the control network layer by designing proper interconnecting matrices. In this paper, the Lyapunov theory is used to demonstrate that the strategy can make the low inertia microgrid still maintain stable against double-layered bounded FDI attacks. The effectiveness of the distributed secondary strategy against bounded FDI attacks is validated in a test microgrid consisting of 4 DGs using the Matlab/Simpower system.